Terahertz-frequency conductivity of charge stripes in the antiferromagnet La5/3Sr1/3NiO4 - Lloyd-Hughes, J; Prabhakaran, D; Castro-Camus, E; Boothroyd, A; Johnston, M; IEEE (2007)
We report the complex refractive index of La5/3Sr1/3NiO4 over the terahertz frequency range, obtained using time-domain spectroscopy. Negligible change in the complex refractive index with magnetic flux densities up to 6T was seen, while changes were observed as the lattice temperature was increased from 1.5 K to the charge-ordering temperature at 220 K. The terahertz frequency response therefore originates from the dielectric function rather than the magnetic permeability.